Transfer coefficients of heavy metals and fatty acid content of total lipids in freshly built beehives in different territories of the Carpathian region - Y. F. Rivis; V. O. Postoienko; B. V. Gutyj; O. I. Stadnytska; I. I. Saranchuk; O. Ya. Klym; A. V. Shelevach; O. B. Diachenko; O. O. Hopanenko; O. O. Bezaltychna; V. M. Yasko (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Гжицького. Серія: Сільськогосподарські науки)
In the literature, there is only fragmentary data on the content of heavy metals and certain forms of fatty acids in freshly built bee combs (tongues) in different territories of the Carpathian region. The work aimed to determine the transfer coefficients of heavy metals from bee combs and abdominal tissues to bee combs and the fatty acid content of total lipids in freshly built bee combs (tongues) in different territories of the Carpathian region. Experimental apiaries of clinically healthy honey bees of the Carpathian breed were selected based on private apiary farms in the mountain, foothills, and forest-steppe territories of the Lviv region. The content of heavy metals in bee pollen, abdominal tissues of honey bees, and freshly built bee combs were studied to determine the transition coefficients. The content of heavy metals in selected samples of bee pollen, abdominal tissues of honey bees, and freshly built bee combs was determined using an atomic absorption spectrophotometer, and the fatty acids of total lipids in the combs were determined using a gas-liquid chromatographic apparatus. It was established that in the direction from the mountain to the foothills and further to the forest-steppe territories of the Carpathian region, the content of Ferrum, Zinc, Cuprum, Cobalt, Chromium, Nicol, Plumbum, and Cadmium in bee pollen (pollen), tissues of the abdomen of honey bees and in freshly built bee combs increases (tongues). In the above direction, the transfer coefficients of Ferrum, Zinc, Copper, Chromium, Nicol, and especially Plumbum and Cadmium from bee pollen to bee combs increase strongly; Ferrum, Zinc, Cobalt, Nicol and especially Lead and Cadmium from abdominal tissues. The total content of esterified forms of fatty acids in bee combs (tongues) obtained from beehives located in the foothills and especially the forest-steppe area of the Carpathian region is lower than in combs selected from beehives located in the mountainous area. The content of fatty acids of total lipids, which are characterized by antimicrobial activity, in freshly built bee combs (tongues) obtained from beehives located in the foothills and forest-steppe areas of the Carpathian region, compared to combs selected from beehives located in the mountainous area, is lower. Freshly built bee combs (tongues) can be bioindicators of the ecological state of the environment. In the future, it is necessary to establish the wax productivity of worker bees in different territories of the Carpathian region and search for ways to obtain high-quality honey in the above region.